Saran Seat Covers...Smart, Modern Patterns Last the Life of Your Car! - Dow Chemical Company (1950)
Color print advertisement for Saran fabric, made from Saran textile monofilaments. Saran is the trade name for polyvinylidene chloride, which can be formed into monofilaments or a thin plastic film. The advertisement features a man and woman in a car with Saran fabric upholstery. A sidebar shows swatches of Saran fabric in plaid and other patterns. A smaller inset illustration shows luggage covered with Saran fabric. The accompanying text promotes the use of Saran fabric for seat covers as well as luggage. This advertisement appeared in The Saturday Evening Post.
Keywords: Dow Chemical Company; Advertising; Chemical industry; Corporations; Plastics; Plastics industry and trade; Textile fabrics; Textile industry; Automobiles--Upholstery; Luggage; Luggage industry; Women in advertising